Perbandingan Regulasi Bank Digital di Indonesia dan Singapura - Michele Febriyanti; Imam Haryanto (Ajudikasi : Jurnal Ilmu Hukum, 2023)
In digital banking, customers who are served digitally can be done starting from the business connection between the bank and the customer starting from opening an account, executing account transactions, to closing a deposit account which is carried out through the use of Information Technology. This of course makes it easier for customers because these activities can be done anywhere. Behind the convenience obtained from using digital banking services, there are also risks involved. Thus, the need for legal protection for customers who use digital banks is necessary to protect consumers from customers in banking services, because the law integrates and serves society. However, unfortunately the regulations regarding Digital Banks in Indonesia have not yet stood alone and are still being reviewed by the OJK. Therefore, so that the special regulations for digital banks in Indonesia can be of good use and not harm any party, references are needed from other countries that have issued legal regulations regarding digital banking to see the legal regulations for digital banks that have been previously implemented in that country so that they can become a reference for the process of making special regulations regarding banking in Indonesia. One country that has implemented special regulations regarding digital banking is Singapore. Based on these problems, in this journal the author will discuss the General and Systematic Overview of Legal Protection for Digital Bank Customers in Indonesia and the Comparison of Digital Bank Regulations in Indonesia and Digital Banks in Singapore for Customers.